Three-dimensional Al-substituted quasi-concentration gradient Ni-Co layered double hydroxide nanosheets for high-performance asymmetric supercapacitors. (December 2020) - Ren, Y.; Du, H.; Zhou, X.; Liu, Y.; Wang, Q.; Li, S.; Wang, W.; Dong, X.
Abstract: Based on an easy-to-operate stepwise electrochemical deposition method, Al-substituted layered bimetallic hydroxide (Ni-Co layered double hydroxide [LDH]) with quasi-concentration gradient (Al-QCG) was deposited on Ni foam. The three-dimensional porous heterostructured Al-QCG could significantly accelerate electron conduction and facilitate electrolyte penetration, effectively improving the specific capacitance and rate performance of the supercapacitor. In addition, Al substitution changed the crystal structure of LDH and prevented local agglomeration and splitting of the layered nanosheets effectively during reproducible charge/discharge cycling, further improving the electrode's cyclic stability. Al-QCG demonstrated an excellent specific capacity of 2372.6 F g −1 at 1 A g −1 and 1180.0 F g −1 at 20 A g −1, and the cycling stability of the Al-QCG/NF electrode greatly improved from 30.0% of bulk Ni–Co LDH to 86.1% after 5000 cycles at 20 A g −1 . The asymmetrical supercapacitors (ASCs) with the activated carbon anode also displayed a high specific capacitance of 48.1 F g −1 at 1 A g −1, and it remained at 56.3% of its capacity when the current density increased to 10 A g −1 . The ASCs achieved a maximum energy density of 15.0 Wh/kg at 763.4 W/kg and an impressive capacitance retention of 90.9% after 10, 000 cycles at 2 A g −1, showing promising application in high-performance supercapacitors. This work highlighted the complex interactions between the composition of different element ratios and multidimensional morphology on the dynamics and capacitive performance of LDH materials. Graphical abstract: Al-substituted quasi-concentration gradient Ni-Co LDH displayed a porous intercalated structure, which enabled excellent electrochemical performance in supercapacitors. LDH, layered double hydroxide. Image 1 Highlights: Al-substituted multilayer Ni-Co layered double hydroxide was prepared by step-by-step electrodeposition. Al substitution creates vacancies for charge transfer and improves conductivity. The quasi-concentration gradient stabilizes the electrode structure in redox reaction. Al-QCG displays excellent specific capacitance and rate and cyclic performance. High energy and power density are obtained in an asymmetry supercapacitor.